2022
DOI: 10.3389/pore.2022.1610479
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Significance, Related Molecular Changes and Tumor Immune Response Analysis of the Abnormal SWI/SNF Complex Subunit PBRM1 in Gastric Adenocarcinoma

Abstract: Background: PBRM1 gene abnormalities were recently found to play a role in tumor development and tumor immune activity. This article will explore the clinicopathological and molecular changes and tumor immune activity of the abnormal SWI/SNF complex subunit PBRM1 in gastric adenocarcinoma (GAC) and its significance.Methods: The cBioPortal, LinkedOmics and TISIDB datasets were used to analyze the abnormality of the PBRM1 gene in GAC and its relationship with prognosis, related molecular changes and tumor-infilt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…31 Furthermore, mutations in PBRM1 are also associated with pancreatic cancer (PDAC), advanced gastric cancer (GC), cervical cancer (CCA) and other tumour formation related. [32][33][34][35][36] [20][21][22][23][24][25][26][27][28][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] In addition, genes encoding tumour-associated subunits of the SWI/SNF complex, such as BAF57/SMARCE1, are heterozygous for mutations or completely lost in familial spinal meningioma cases. 31 Some of these tumours contain mutations in more than one subunit, such as renal cell carcinoma, breast cancer, and colon cancer, suggesting that the development of a cancer may be caused by mutations in one or more subunits of the SWI/ SNF complex.…”
Section: Mutati On S In Swi/s Nf Subunits C Aus E Human Tumour Smentioning
confidence: 99%
See 1 more Smart Citation
“…31 Furthermore, mutations in PBRM1 are also associated with pancreatic cancer (PDAC), advanced gastric cancer (GC), cervical cancer (CCA) and other tumour formation related. [32][33][34][35][36] [20][21][22][23][24][25][26][27][28][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] In addition, genes encoding tumour-associated subunits of the SWI/SNF complex, such as BAF57/SMARCE1, are heterozygous for mutations or completely lost in familial spinal meningioma cases. 31 Some of these tumours contain mutations in more than one subunit, such as renal cell carcinoma, breast cancer, and colon cancer, suggesting that the development of a cancer may be caused by mutations in one or more subunits of the SWI/ SNF complex.…”
Section: Mutati On S In Swi/s Nf Subunits C Aus E Human Tumour Smentioning
confidence: 99%
“…PBRM1, a target subunit of PBAF, is a common oncogene with a 40% mutation rate in renal cell carcinoma, and our previous study found that deletion of PBRM1 could activate the AKT pathway and glycolytic pathway and thus affect the function of ccRCC cells 31 . Furthermore, mutations in PBRM1 are also associated with pancreatic cancer (PDAC), advanced gastric cancer (GC), cervical cancer (CCA) and other tumour formation related 32–36 . BRD7, SMARCC2, ARID2, ACTL6A/B, SMARCC1, SMARCD1/2/3 are other key subunits of SWI/SNF, and recent studies have reported that mutations in these subunits cause gastric cancer (GC), colon cancer (CRC), hepatocellular carcinoma (HCC), head and neck squamous carcinoma (HSNC), breast cancer (BRCA) and other tumours 20–28,37–53 .…”
Section: Mutations In Swi/snf Subunits Cause Human Tumoursmentioning
confidence: 99%